Viscous shear resistance of deformation in nominally immobile friction contact - Костогриз, С.Г.; Шалапко, Ю.І.; Мисліборський, В.В. (Problems of Tribology, 2014)
The paper a show that into space is recently called "third body" in the contacting surfaces, and a viscous shear resistance was occurs. The dependence of the thickness of the "third body" from the shear modulus of materials and the tangential stiffness of contacting surfaces was base. Revealed the equivalently coefficient of viscous resistance in the contact from the thickness of the "third body", the shear modulus, tangential contact stiffness and a nominal specific friction. The coefficient of viscous resistance on basis of experimental data that were processing oscillograms of free damping oscillations of contacts was defined.